Carboxylic Acid Bioisosteres in Medicinal Chemistry: Synthesis and Properties. (19th May 2022) - Bredael, Kato; Geurs, Silke; Clarisse, Dorien; De Bosscher, Karolien; D'hooghe, Matthias
Abstract : Lead optimization represents the tedious process of fine-tuning lead compounds from biologically active hits to suitable drug candidates for clinical trials. By chemically modifying a hit structure, an improved compound can be obtained in terms of activity, selectivity, and pharmacokinetic ADME (absorption, distribution, metabolism, and excretion) properties. The carboxylic acid moiety is known to be a crucial functionality in many pharmaceutically active compounds. Despite its common use as a key functionality in drugs, its presence in a lead molecule is often associated with poor pharmacokinetic properties and toxicity. In this literature overview, we discuss how the shortcomings of a carboxylic acid can be circumvented by replacing this functionality with bioisosteres. In this way, the positive aspects of this moiety, such as its activity, for example, by virtue of its capacity to form hydrogen bonds, can be maintained or even improved. To that end, we provide an overview of the most promising carboxylic acid bioisosteres and discuss a selection of synthetic routes towards the main functionalities.